Range-wide priority setting for the conservation and restoration of Asian rosewood species accounting for multiple threats and ecogeographic diversity - Gaisberger, Hannes; Fremout, Tobias; So, Thea; Thammavong, Bansa; Bounithiphonh, Chaloun; Hoa, Tran Tin; Yongqi, Zheng; Kanchanarak, Tania; Changtragoon, Suchitra; Sreng, Sineath; Ping, Huang; Hang Hung, Tin; et al. (Elsevier, 2022)
Understanding the impact of multiple anthropogenic threats on tree species is urgently needed for estimating population decline and enabling coordinated and efficient conservation actions. We applied a spatially explicit framework to assess the vulnerability of three highly valuable Asian rosewood species (Dalbergia cochinchinensis, D. cultrata, D. oliveri) to five key threats across their native ranges in six countries of the Greater Mekong Subregion. All three species face significant threat levels from at least one of the five threats in more than 75% of their native ranges, including within existing protected areas. Overexploitation is the single most important threat (53–60%), followed by habitat conversion (17–41%) and fire (20–28%). About 21% of the distribution range of D. cultrata is under medium to very high threat from climate change, which is predicted to have less impact on D. oliveri and on D. cochinchinensis. Based on our threat assessment we delineated species-specific priority areas for conservation and restoration that we subdivided by ecoregions as a surrogate for adaptive variation within species. Half of the ecoregions were classified as priority for improving the conservation of adaptive variation in one or more of the species. We propose spatially explicit follow-up actions that include in situ conservation, restoration, and ex situ conservation to improve the effectiveness of current conservation measures to capture adaptive variation within species. Transboundary coordination will be important to effectively address conservation threats. The study can act as a model for regional planning for other valuable tree species.